OER Handbook for Eastern North Carolina - Seibert, Heather; Hoover, Jeanne K.; Zuberbier, Dan (My University, 2019)
For this project, we developed an introductory handbook giving interested educators a basic overview of Open Educational Resources (OER), and suggestions on how to integrate them into their courses. As the popularity of OER has grown, the number of resources on OER have increased as well. Organizations, like the Open Textbook Network, have created guides on using, producing, and editing OER. Additionally, there are comprehensive books and Libguides on this topic. However, we identified a gap in these resources. The ideal audience for this handbook is someone who wants a basic understanding of OER: what they are, where to find them, and how to use them. Additionally, we produced a brief infographic detailing steps to create an OER.
Keywords: Open Educational Resources; Creative Commons